Shadow Economies Around the World : Size, Causes, and Consequences - Schneider, Friedrich (IMF Working Papers; Working Paper ;, 2000)
This paper presents estimates of the size of the shadow economy in 76 developing, transition, and OECD countries, which are derived by combining figures from different estimation methods. We describe and discuss the strengths and weaknesses of the different estimation methods. We find that the growth of the shadow economy-which is now remarkably large in the 76 countries-is strongly related to increasing burdens of taxation and social security contributions, as well as to the extent of state regulatory activities. Rising corruption also has a clearly positive impact on the growth of the shadow economy.